Preservation potential of ancient plankton DNA in Pleistocene marine sediments - Boere, A.; Rijpstra, W.; De Lange, G.; Sinninghe Damsté, J.; Coolen, Marco (2011)
Recent studies have shown that ancient plankton DNA can be recovered from Holocene lacustrine and marine sediments, including from species that do not leave diagnostic microscopic fossils in the sediment record. Therefore, the analysis of this so-called fossil plankton DNA is a promising approach for refining paleoecological and paleoenvironmental information. However, further studies are needed to reveal whether DNA of past plankton is preserved beyond the Holocene. Here, we identified past eukaryotic plankton members based on 18S rRNA gene profiling in eastern Mediterranean Holocene and Pleistocene sapropels S1 (~9ka), S3 (~80ka), S4 (~105ka), and S5 (~125ka). The majority of preserved ~400- to 500-bp-long 18S rDNA fragments of microalgae that were studied in detail (i.e. from haptophyte algae and dinoflagellates) were found in the youngest sapropel S1, whereas their specific lipid biomarkers (long-chain alkenones and dinosterol) were also abundant in sediments deposited between 80 and 124ka BP. The late-Pleistocene sediments mainly contained eukaryotic DNA of marine fungi and from terrestrial plants, which could have been introduced via the river Nile at the time of deposition and preserved in pollen grains. A parallel analysis of Branched and Isoprenoid Tetraethers (i.e. BIT index) showed that most of the organic matter in the eastern Mediterranean sediment record was of marine (e.g. pelagic) origin. Therefore, the predominance of terrestrial plant DNA over plankton DNA in older sapropels suggests a preferential degradation of marine plankton DNA.